Engraved Gems : From antiquity to the present. - Van den Bercken, Ben (PALMA., 2017)
Many are no larger than a fingertip. They are engraved with symbols, magic spells and images of gods, animals and emperors. These stones were used for various purposes. The earliest ones served as seals for making impressions in soft materials. Later engraved gems were worn or carried as personal ornaments - usually rings, but sometimes talismans or amulets. The exquisite engraved designs were thought to imbue the gems with special powers. For example, the gods and rituals depicted on cylinder seals from Mesopotamia were thought to protect property and to lend force to agreements marked with t.